Blogging as a tool in developing writing skills: lessons from the experience of the students and class teacher - Abdul Ghani, Rozina; Ahmat, Mas Azila; Mohd. Asraf, Ratnawati (English Language Education Publishing, 2017)
Blogging is often seen as an online tool that promotes authentic and interactive communication that could realize the collaborative demands of a task-based classroom. This has triggered the interest of language practitioners and researchers alike in its value in developing language skills. This paper describes a study that was aimed at discerning the students’ and their class teacher’s views toward blogging in their writing classroom. Specifically, it delved into the use of this asynchronous online medium in the teaching of writing. The participants were the teacher and the 25 ESL students of a writing class, where most of the tutorials were conducted online and where all the writing activities were posted on the students’ blogs. The data were collected using the Students’ Perception Questionnaire and the teacher’s reflective log of her teaching. The findings suggest that although the students were intrigued by the novelty of using blogs in language learning, several considerations need to be made as this online medium is challenging for both the learners and the teacher.